Assessment of Moral Injury in Veterans and Active Duty Military Personnel With PTSD: A Review - Koenig, Harold G.; Youssef, Nagy A.; Pearce, Michelle (Frontiers in Psychiatry, 2019)
Background: Moral Injury (MI) involves “a deep sense of transgression including feelings of shame, grief, meaninglessness, and remorse from having violated core moral beliefs” (Litz et al., 2009). MI is often found in Veterans and Active Duty Military personnel with posttraumatic stress disorder (PTSD). MI is widespread among those with PTSD symptoms, adversely affects mental health, and may increase risk of suicide; however, MI is often ignored and neglected by mental health professionals who focus their attention on PTSD only. Methods: A review of the literature between 1980-2018 conducted in 2018 is presented here to identify scales used to assess MI. Databases used in this review were PsychInfo, PubMed (Medline), and Google Scholar. Search terms were “moral injury,” “measuring”, “screening,” “Veterans,” and “Active Duty Military.” Inclusion criteria were quantitative measurement of MI and health outcomes, Veteran or Active Duty Military status, and peer-review publication. Results: Of the 730 studies identified, most did not meet eligibility criteria, leaving 118 full text articles that were reviewed, of which 42 did not meet eligibility criteria. Of the remaining 76 studies, 34 were duplicates leaving 42 studies, most published in 2013 or later. Of 22 studies that assessed MI, five used scales assessing multiple dimensions and 17 assessed only one or two aspects (e.g., guilt, shame, or forgiveness). The remaining 20 studies used one of the scales reported in the first 22. Of the five scales assessing multiple dimensions of MI, two assess both morally injurious events and symptoms and the remaining three assess symptoms only. All studies were cross-sectional, except three that tested interventions. Conclusions: Moral injury in the military setting is widespread and associated with PTSD symptom severity, anxiety, depression, and risk of suicide in current or former military personnel. Numerous measures exist to assess various dimensions of MI, including five multi-dimensional scales, although future research is needed to identify cutoff scores and clinically significant change scores. Three multi-dimensional measures assess MI symptoms alone (not events) and may be useful for determining if treatments directed at MI may reduce both symptoms and impact other mental health outcomes including PTSD.